2006
DOI: 10.1017/s0025315406014366
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for benthic body size miniaturization in the deep sea

Abstract: The benthic body size miniaturization hypothesis states that deep-sea communities are dominated by organisms of smaller body size, although some ¢eld studies have produced contradictory results. Using appropriate sample sets, this study tests this hypothesis by contrasting the benthic communities of the Fladen Ground (North Sea, 150 m) and the Faroe^Shetland Channel (1600 m). Samples were collected for large (500 mm) and small macrofauna (250^355 mm), meiofauna (45 mm) as well as an intermediate sized 'mesofau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Transitions from larger to smaller body size dominance during lower food supplies also confirm hypotheses from spatial studies (12,17,18) that food availability influences interspecific bodysize distributions of deep-sea macrofauna. Overall the monthly average biomass (per capita TA B ) correlated positively with POC flux with a lag of ϳ7 months (r s ϭ 0.60, n ϭ 21, P ϭ 0.004) (Fig.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Transitions from larger to smaller body size dominance during lower food supplies also confirm hypotheses from spatial studies (12,17,18) that food availability influences interspecific bodysize distributions of deep-sea macrofauna. Overall the monthly average biomass (per capita TA B ) correlated positively with POC flux with a lag of ϳ7 months (r s ϭ 0.60, n ϭ 21, P ϭ 0.004) (Fig.…”
supporting
confidence: 74%
“…For example, a metaanalysis of samples collected from 1961 to 1985 in the western North Atlantic found that the principal pattern of macrofauna abundance was related to depth-corrected POC flux as determined from the more modern sea-viewing wide fieldof-view sensor (SeaWiFS) ocean color data (13). Analysis of patterns in body size distributions have also found a decrease in average body size with increasing depth and/or decreasing food availability (12,17,18).Time-series research of abyssal communities has been more limited. Previous time-series studies have comprehensively described deep-sea community collapses that occurred in synchrony to glaciations (19) and centennial-scale climate variations since the time of the last glacial maximum (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meiofauna are conventionally defined to include animals that pass through a 1000-μm mesh sieve and are retained on a 63-μm mesh sieve (Giere, 1993). However, because deep-sea organisms are generally smaller than their shallow-water counterparts (Kaariainen & Bett, 2006), a 32-μm mesh sieve was used as the lower limit in this study. Meiofauna were extracted by density gradient centrifugation with Ludox as a flotation medium (de Jonge & Bouwman, 1977).…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…This method is commonly employed to assess body size abundance relationships when sampled individuals are too numerous and the species are hard to recognize, as occur in benthic macroinvertebrate assemblages (Dinmore & Jennings, 2004;Drgas, Radziejewska, & Warzocha 1998;Kaariainen & Bett, 2006;Mancinelli, Pinna, & Basset, 2008;Mouillot et al, 2006).…”
Section: Environmental Variablesmentioning
confidence: 99%